Implementasi Model Inkola (Informasi, Komunikasi, dan Tatakelola) dalam Pengelolaan Anak Penyandang Diabetes Tipe 1 pada Program Pengembangan Desa Sehat di Wilayah Bandung Raya dan Cimahi - Widiawati, Ida; Rumahorbo, Hotma; Sasmita, Anah; Kusniasih, Susi; Nurhayati, Betty; Damayanti, Didit (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
There is an increasing number of cases of children with type 1 diabetes in the community, especially in the Greater Bandung area and Cimahi City, there are 50 children with diabetes who need special treatment. The InKoLa (Information, Communication and Governance) model is a sustainable care model that has been empirically proven to improve the quality of life of children with diabetes and control blood sugar. The purpose of implementing the InKoLa Model is to improve the ability and independence of parents in caring for children and improve the ability of teachers/school parties to assist children at school and provide optimal health services by Puskesmas health workers. This model was implemented using training/education and mentoring methods in partner areas with a target group of 30 children and parents, 10 teachers/school officials and 12 Puskesmas health workers. The increase in parents' knowledge in the good category by 43.3%, high self-efficacy increased by 43.5%; UKS teacher knowledge in the good category increased by 40% and high self-efficacy increased by 40%. Children's knowledge in the good category increased by 42.6% and self-efficacy increased by 60%. The meeting resulted in a common perception and commitment to bring optimal information, communication and governance at home and school. The INKOLA model was implemented to manage children with type 1 diabetes in the community. It is recommended that the Health Office and Puskesmas use the InKoLa model to manage children with type 1 diabetes in the community.